Selective manipulation of excitatory and inhibitory neurons in top-down and bottom-up visual pathways using ultrasound stimulation - Yehhyun Jo; Xiaojia Liang; Hong Hanh Nguyen; Yeonseo Choi; Minji Choi; Ga-Eun Bae; Yakdol Cho; Jiwan Woo; Hyunjoo Jenny Lee (Brain Stimulation)
Introduction: Techniques for precise manipulation of neurons in specific neural pathways are crucial for excitatory/inhibitory (E/I) balance and investigation of complex brain circuits. Low-intensity focused ultrasound stimulation (LIFUS) has emerged as a promising tool for noninvasive deep-brain targeting at high spatial resolution. However, there is a lack of studies that extensively investigate the modulation of top-down and bottom-up corticothalamic circuits via selective manipulation of excitatory and inhibitory neurons. Here, a comprehensive methodology using electrophysiological recording and c-Fos staining is employed to demonstrate pulse repetition frequency (PRF)-dependent E/I selectivity of ultrasound stimulation in the top-down and bottom-up corticothalamic pathways of the visual circuit in rodents. Materials and methods: Ultrasound stimulation at various PRFs is applied to either the lateral posterior nucleus of the thalamus (LP) or the primary visual cortex (V1), and multi-channel single-unit activity is recorded from the V1 using a silicon probe. Results and conclusion: Our results demonstrate that high-frequency PRFs, particularly at 3 kHz and 1 kHz, are effective at activating the bidirectional corticothalamic visual pathway. In addition, brain region-specific PRFs modulate E/I cortical signals, corticothalamic projections, and synaptic neurotransmission, which is imperative for circuit-specific applications and behavioral studies.